Performance of soybean (Glycine max) genotypes on diferent sowing dates and row spacings in Vertisols - BILLORE, S D; JOSHI, O P; RAMESH, R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted for two years (1994-95) in rainy season to evaluate the performance of soybean (Glycine max (L.) Merr.) genotypes under 5 sowing dates and 2 row spacings. The average soybean seed yield decreased linearly’by 181.77 kg/ha for every 5 days delay in sowing from the normal date (25 June). The maximum reduction in seed yield was recorded in ’JS 71-05’ followed by ’Ahilya 3’,’JS 335’,’Ahilya 1’ and ’PK 472’ as evidenced from the regression equations. However, genotype ’Ahilya 3’ sustained higher yield levels over sowing dates. The narrow row (30cm) showed an-edge over wider row (45 cm) spacing. Delayed planting significantly reduced the protein and oil content of soybean. The maximum oil and protein content was recorded in ’Ahilya 3’ and ’JS 335’, respectively. Wider row planting showed superiority over the narrow row width with regards to oil content.